منهج الإمام الطبري في إيراد القراءات الشاذة في تفسيره - Nor Hafizi, Yusof; Mohamed Fathy, Mohamed Abdelgelil (2020)
This research presents a statement of the formulas used by Altabari where he had expressed in his choice of reading, his criticism and also his correction of some of the readings and not all. He sometimes uses the phrase " I cannot read it" or was marveled at some of the correct readings and his response to them, and other formulas that he used to express his choice for some readings over other readings. This study also showed the types mentioned by Ibn Jarir in his Tafsir (interpretations). We find out that he was not limited to one type of readings but also listed many types including Almaqboul (acceptable) and Almashhour (famous) and many others. Ibn Jarir relied on the criteria that he used in his readings. Ibn Jarir had agreed on certain placements in his readings with other scholars and readers and he mentioned his reason for agreeing. But disagreed with readers in other placements. He also mentioned his reason for his disagreement with readers as well as his argument on that. Ibn Jarir explained at the beginning of his Tafsir (interpretations) that reading is Sunnah and if proven cannot be returned to its Sunnah. Al Tabari did not adhere to what he had committed himself to what he mentioned in his Tafsir, and he may respond to some recurring readings on the pretext of disagreeing with scholars of Tafsir. Or when he reads solo from the rest of readers about the argument. His reading is often based on the pretext that the argument has more than three readers. He may have corrected abnormal readings and made it permissible on the pretext of its correctness in Arabic without considering its validity of its origin and approval to write The Ottoman Quran. And the result is that Ibn Jarir did not adhere to the method he mentioned in his Tafsir. And that is probably due to the involvement of Altabari and his skill in this domain, there is no need to elaborate nor fully adjust his method, as well as because he lived in a time full of scientists and readers interested in this great science which does not need clarification more than mentioned because it is known to them.